One-pot synthesis of iminoimidazolines under microwave irradiation in solvent-free conditions - Servi, Sueleyman; Genc, Murat (Taylor & Francis Inc, 2007)
Substituted iminoimidazolines were synthesized from a one-pot reaction of aromatic or hetero-aromatic amines with imidazolidine-2-thione under solvent-free conditions using microwave irradiation with good to excellent yields.
Keywords: imidazolidine-2-thione; iminoimidazoline; microwave irradiation; one-pot synthesis